Exploring the Relationship between Mental Workload, Variation in Performance and Physiological Parameters. Issue 19 (2016) - Marinescu, A.; Sharples, S.; Ritchie, A.C.; López, T. Sánchez; McDowell, M.; Morvan, H.
Abstract: Real time non-intrusive mental workload level estimation may lead to significant improvements in the design and operation of future flight decks, reducing the cognitive demand on pilots. This study explores the relationship between mental workload, variation of performance and objective physiological measures. The study presented was performed in laboratory conditions and required participants to perform a custom-designed tracking task with elements of mental arithmetic that imposed varying levels of mental workload. The data collected consisted of: physiological measurements (heart inter-beat intervals, breathing rate, facial thermography); subjective ratings of workload from the participants (ISA and NASA-TLX); and the performance measured within the task. Initial results suggest facial thermography as a good candidate for non-intrusive mental workload measurements as temperature variations on some areas, for example the nose, appear to relate well to the changes in mental workload level as measured by subjective ratings as well as performance measures on performing the task.